Desarrollo de recurso pedagógico interactivo para valorizar la iconografía y sonidos originarios de la cultura Puruhá en Cacha, provincia de Chimborazo, Ecuador durante el periodo mayo-septiembre 2021 - Cabezas Mancero, David Andrés (2022)
Resource to value the iconography and sounds originating from the Puruhá culture in Cacha, Chimborazo province, Ecuador during the period May – September 2021. (Degree Thesis). National University of Chimborazo. Riobamba, Ecuador. Ecuador is a multicultural country with a very distinctive cultural heritage. Despite the influence of other cultures by means of migration and globalization, the country has stayed true to its roots. However, over time new generations are losing interest in culture, mainly due to the folklorization of many of our traditions and the excessive input of information available on digital media today. The purpose of this research was to determine the importance of developing an interactive pedagogical resource to enhance value to the iconography and sounds of the Puruwa culture in Cacha, Chimborazo province - Ecuador. Although it is oriented to children, this resource can be used by anyone. On the other hand, the methodology has a mixed approach, that is, the research development and data collection were approached with qualitative and quantitative resources. Likewise, thanks to a pre-experimental desing, we were able to determine the effect, incidence and importance of the interactive pedagogical resource. The experimental implementation of this pedagogical resource made it possible for children to interpret sounds and symbols. Thus, they were able to achieve acceptance and association with aspects of their daily lives, as well as familiarize themselves with these sounds despite their conceptual unawareness. This application not only helps to preserve identity, but also allows to become aware of it. Hence the importance of producing educational material that can promote questioning about the approach of culture as a relevant and necessary topic.